IN VIVO ANTITRYPANOSOMAL EFFECTS OF SOME ETHNOMEDICINAL PLANTS FROM NUPELAND OF NORTH CENTRAL NIGERIA - Mann, A.; Ifarajimi, O. R.; Adewoye, A. T.; Ukam, C.; Udeme, E. E.; Okorie, I. I.; Sakpe, M. S.; Ibrahim, D. R.; Yahaya, Y. A.; Kabir, A. Y.; Ogbadoyi, E. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Four medicinal plants Acacia nilotica, Bombax buonopozense, Terminalia avicennioides and Zanthoxylum zanthoxyloides traditionally used for treatment of sleeping sickness in Nupeland were investigated for in vivo antitrypanosomal activity. Methanol extracts of different parts of each plant (stem barks and fruits) were obtained and evaluated for their in vivo antitrypanosomal activities against Trypanosoma brucei brucei. Phytochemical screening of the methanol extracts of each plant were performed by standard procedures. Methanol extracts of A. nilotica (stem bark), B. buonopozense (stem bark), T. avicennioides (round fruit) and Z. zanthoxyloides (stem bark) were effective on trypanosomes. The extracts of A. nilotica and B. buonopozense exhibited antitrypanosomal effects at 200 and 300 mg/kg body weight respectively. Doses were able to clear the parasites from circulation within 6 and 7 days of treatment respectively with prolonging survival period of up to 30 days. While the extracts of T. avicennioides and Z. zanthoxyloides showed trypanostatic effects and could not clear the parasites completely. The methanol extracts of these plants contain metabolites that are associated with antitrypanosomal effects; therefore, these medicinal plants may be sources of new compounds that may be active against T. b. brucei. This study has also justified the claim that some medicinal plants of Nupeland possess antitrypanosomal activity and could be useful in the management of trypanosomiasis.